Education Game of Multiplying Based on Horizontal Method of HTML 5 and Android - Ricky, Michael Yoseph (Bina Nusantara University, 2015)
Over the years, technology is growing rapidly followed by the development of game and its variations. Now, game is easily found on a mobile device. Moreover, game on mobile device can also be used as an excellent medium for learning or often referred as educational game because the nature of educational game is practical, easy to carry anywhere, and tends to be fun. This research was to create a mobile game application for learning with Horizontal method based on HTML 5 and Phonegap and to introduce the method as a method of mathematical multiplication process. This research used the Scrum method for program development. The results obtained showed that the game in this study is considered attractive and received a positive response from the player. Player also found it helpful to know the patterns of mathematics through the multiplication ofnumbers in this game. So through this game the player can perform mathematical multiplication calculations quickly.